An empirical study of DEBT maturity structure and determinants for public and private DEBT securities in Malaysia and Singapore - Abdul Wahab, Noor Maimun; Md Nassir, Annuar; Abdul Rahim, Norhuda; Ab Razak, Nazrul Hisyam (International Journal of Advanced Science and Technology, 2020)
for debt maturity structure of public and private debt securities in Malaysia and Singapore. The determinant’s model of this study incorporates three common factors namely breadth of the debt market, credit ratings and corporate taxation and three main theories (signaling and liquidity theory, asymmetric information, trade off and tax clientele effect theory) are utilized in proving the relationships amongst aforesaid common factors and debt maturity structure (the dependent variable). The result of the current research signifies that the decision of companies in Malaysia and Singapore with respect to debt maturity structure in the past is profoundly dependent on its current and future debt maturity structure. The finding is also in agreement with existing theories and past empirical evidence which state that both the breadth of the debt market and corporate taxation play significant roles in influencing debt maturity structure for private debt securities in Malaysia. On the other hand, the current research provides evidence that corporate taxation is also an important determinant that affects debt maturity structure for public debt securities in Malaysia. Meanwhile, it was also revealed that Singaporean firms with better credit ratings tend to raise more long-term private debt securities and lower usage of public debt securities. In the case of Malaysia, firms with better credit ratings utilise less long-term public debt securities compared to short term debts. This research can be used for the universities, teachers and students. In this research, the model of the An Empirical Study of DEBT Maturity Structure and Determinants for Public and Private DEBT Securities in Malaysia and Singapore is presented in a comprehensive and complete manner.